Long-term commuting times and air quality relationship to COVID-19 in São Paulo. (May 2022) - Pérez-Martínez, P.J.; Dunck, J.A.; de Assunção, J.V.; Connerton, P.; Slovic, A.D.; Ribeiro, H.; Miranda, R.M.
Abstract: The Coronavirus Disease 2019 (COVID-19) epidemic is an unprecedented global health crisis and the effects may be related to environmental and socio-economic factors. In São Paulo, Brazil, the first death occurred in March 2020 and since then the numbers have grown to 175 new deaths per day in April 2021, positioning the city as the epicenter of the number of cases and deaths in Brazil. São Paulo is one of the largest cities in the world with more than 12 million inhabitants, a fleet of about 8 million vehicles and frequent pollutant concentrations above recommended values. Social inequalities are evident in the municipality, similarly to other cities in the world. This paper focuses on transportation activities related to air pollution and associated with cardiovascular and respiratory diseases especially on people who developed comorbidities during their whole life. This study relates travel trip data to air quality analysis and expanded to COVID-19 disease. This work studied the relationship of deaths in São Paulo due to COVID-19 with demographic density, with family income, with the use of public transport and with atmospheric pollution for the period between March 17th, 2020 and April 29th, 2021. The main results showed that generally passenger kilometers traveled, commuting times and air quality related diseases increase with residential distance from the city center, and thus, with decreasing residential density. PM2.5 concentrations are positively correlated with COVID-19 deaths, regions with high urban densities have higher numbers of deaths and long-distance frequent trips can contribute to spread of the disease. Highlights: Mobility, air-quality, sociodemographic and COVID-19 data were related. Personal exposure levels differ by type of activity, transport mode and income classes. Private cars contribute to worsening air quality and affect the health of transit users. Reducing traffic commuting times is crucial to prevent air pollution related diseases. Public policies must be employed to improve living conditions of peripherical regions.